2021
DOI: 10.3399/bjgpo.2021.0150
|View full text |Cite
|
Sign up to set email alerts
|

Deaths from cardiovascular disease involving anticoagulants: a systematic synthesis of coroners’ case reports

Abstract: BackgroundThe global burden of cardiovascular disease (CVD) is forecast to increase, and anticoagulants will remain important medicines for its management. Coroners' Prevention of Future Death reports (PFDs) provide valuable insights that may enable safer and more effective use of these agents.AimTo identify CVD-related PFDs involving anticoagulants.Design and SettingRetrospective observational study of coronial case reports in England and Wales between 2013 and 2019.MethodWe screened 3037 PFDs for eligibility… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 22 publications
2
43
1
Order By: Relevance
“…This may also require alterations to the content and recipients of PFDs to facilitate the learning of lessons elsewhere, such that they are also designed to provide general information to third parties. Our research, alongside other studies (10,12,24,34,(38)(39)(40)(41)(42)(43), highlights that PFDs contain a wealth of important information that has merit for wide dissemination. However, crucial information in PFDs is often missing, incorrect, or inconsistent.…”
Section: Interpretation and Implications For Clinicians And Policymakersmentioning
confidence: 53%
See 1 more Smart Citation
“…This may also require alterations to the content and recipients of PFDs to facilitate the learning of lessons elsewhere, such that they are also designed to provide general information to third parties. Our research, alongside other studies (10,12,24,34,(38)(39)(40)(41)(42)(43), highlights that PFDs contain a wealth of important information that has merit for wide dissemination. However, crucial information in PFDs is often missing, incorrect, or inconsistent.…”
Section: Interpretation and Implications For Clinicians And Policymakersmentioning
confidence: 53%
“…This difference can be attributed to the quality of our data collection methods, which allowed us to examine all available PFDs to which medicines contributed. Compared with previous studies (10)(11)(12)24,34), concerns reported by coroners were the same, except for those relating to patient safety, which has not been identified in PFDs before. However, in a study examining hospital incident reports, 18% of concerns were related to patient safety (35).…”
Section: Comparison With Previous Literaturementioning
confidence: 56%
“…[6][7][8][9] Case series of PFDs have also been conducted to investigate preventable deaths from medicines and misused drugs, suicides, cardiovascular disease and cycling. [10][11][12][13] During the COVID-19 pandemic, healthcare professionals in England and Wales called for the deaths of their colleagues to be reported to coroners and for PFDs to be issued. 14 15 However, PFDs issued during the COVID-19 pandemic have not been analysed.…”
Section: Primary Carementioning
confidence: 99%
“…6 These reports, named Prevent Future Deaths (PFDs) are now mandated by the Coroners and Justice Act 2009 and the Coroners (Investigations) Regulations 2013. 7,8 Studies have systematically analysed PFDs to assess deaths during the COVID-19 pandemic, involving anticoagulants, medicines purchased online, medication errors and adverse drug reactions [9][10][11][12][13] . A case series of medicine-related PFDs showed that opioids were the most common drug involved in deaths.…”
Section: Introductionmentioning
confidence: 99%